2015
DOI: 10.1111/odi.12378
|View full text |Cite
|
Sign up to set email alerts
|

The role of cathepsin K in oral and maxillofacial disorders

Abstract: Cathepsin K (CTSK) was thought to be a collagenase, specifically expressed by osteoclasts, and played an important role in bone resorption. However, more and more research found that CTSK was expressed in more extensive cells, tissues, and organs. It may not only participate in regulating human physiological activity, but also be closely related to a variety of disease. In this review, we highlight the relationship between CTSK and oral and maxillofacial disorders on the following three aspects: oral and maxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 92 publications
0
21
0
1
Order By: Relevance
“…CatK gene mutations in humans lead to an autosomal recessive disease termed as pycnodysostosis, a specific type of osteopetrosis, characterised by osteosclerosis with increased bone fragility (Gelb et al , ). Recently, CatK has been reported to be distributed in other types of cells, such as macrophages, dendritic cells, adipocytes, fibroblasts, vascular smooth muscle cells and other tissues including lung, heart, colon, skeletal muscle, ovary and placenta (Wen et al , ). Siponen et al () have recently shown by immunohistochemical analyses that CatK is expressed by melanocytes and macrophages, and sporadically in basal keratinocytes and endothelial cells, and that small amounts of CatK also exist extracellularly as well as intracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…CatK gene mutations in humans lead to an autosomal recessive disease termed as pycnodysostosis, a specific type of osteopetrosis, characterised by osteosclerosis with increased bone fragility (Gelb et al , ). Recently, CatK has been reported to be distributed in other types of cells, such as macrophages, dendritic cells, adipocytes, fibroblasts, vascular smooth muscle cells and other tissues including lung, heart, colon, skeletal muscle, ovary and placenta (Wen et al , ). Siponen et al () have recently shown by immunohistochemical analyses that CatK is expressed by melanocytes and macrophages, and sporadically in basal keratinocytes and endothelial cells, and that small amounts of CatK also exist extracellularly as well as intracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…Cat K has a role in many physiological and pathological processes, like embryonic development, brain and thyroid gland physiology, osteoporosis, inflammatory joint diseases, lung and cardiovascular diseases, and cancer . Regarding oral diseases, some of the first reports indicated that Cat K is involved in peri‐implantitis and periodontitis by demonstrating the enzyme in the gingival crevicular fluid . Several studies have later confirmed the important role of Cat K in periodontal disease .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding oral diseases, some of the first reports indicated that Cat K is involved in peri‐implantitis and periodontitis by demonstrating the enzyme in the gingival crevicular fluid . Several studies have later confirmed the important role of Cat K in periodontal disease . Cat K is implicated also in periapical bone loss and inflammation associated with endodontic disease .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is hypothesized that upregulating CTSK expression in a controlled manner to promote the cementogenic/osteogenic differentiation of healthy PDLSCs for tissue engineering‐based periodontal regeneration would not lead to the deterioration of periodontal tissues (Wen et al . ). Although the specific mechanisms underlying the CTSK‐mediated regulation of the multilineage differentiation of PDLSCs are still unclear, it is speculated that these mechanisms may be related to the role of CTSK in molecular signalling regulation, which sharply contradicts the generally accepted collagen‐degradative role of CTSK.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggested that CTSK may also play a role in regulating cementum development. Thus, CTSK probably plays a role in periodontal hard tissue (consisting of alveolar bone and cementum) regeneration (Wen et al ., ). However, the source of CTSK in the periodontal environment and the exact role of CTSK in periodontal regeneration remain unknown.…”
Section: Introductionmentioning
confidence: 97%